Attitude towards genetically modified soybean amongst the Klang Valley stakeholders - Latifah Amin; Jamaluddin Md. Jahi; Abd Rahim Md Nor; Mohamad Osman; Nor Muhammad Mahadi (Environmental Management Society, Malaysia, 2007)
Public acceptance can be understood as the combined attitude of individuals on certain political issues, such as those arising from technological innovations. Other studies have concluded that the public’s attitude towards biotechnology was primarily driven by several factors such as the perceived benefits, risks, moral concerns and encouragement. Risk perception studies have identified two additional important factors named as familiarity and risk acceptance. The purpose of this paper is to study the attitude of the Malaysian public in the Klang Valley region towards genetically modified soybean. A survey was carried out on 1017 respondents from various interest groups in the Klang Valley region. Results of the survey have shown that the overall mean scores for familiarity, perceived benefits, perceived risks, moral concerns and encouragement of GM soybean were moderate. ANOVAs showed significant differences in the six dimensions of attitude across stakeholders’ groups